Penerapan Hidup Bersih dan Sehat Pada Adaptasi Kebiasaan Baru di Tengah Pandemi Covid- 19 Tahun 2020 - Herawati Jaya; Intan Kumalasari; Intan Kumalasari (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
The government’s policy regarding the spread of Corona Virus Disease 2019 (COVID-19) with the number of cases and/or the number of deaths has increased and spread across regions and across countries and has an impact on the political, economic, social, cultural, defense and security aspects, as well as the welfare of the people in Indonesia; The purpose of this study was to find out the Implementation of Clean and Healthy Living (PHBS) in the Adaptation Period of New Habits in the Midst of the Covid 19 Pandemic. This study used the Self-Administered Questionnaire technique which is a data collection technique method by submitting or sending a list of questions to be filled in by themselves. Respondents with a relatively shorter time (Al Adawiyah and Dewi, 2020). This study uses a quantitative method with a survey design, data collection online via Google form. The results of the study were as follows that the knowledge of respondents about PHBS in the medium category was 66 respondents (61.1%), with 34 respondents in the low category (31.5%) and in the high category as many as 8 respondents (7.4%). Meanwhile, for the attitude category, there were 73 respondents (68%), while the low category was 19 respondents (18%) and the high category was 16 respondents (15%), the need for awareness to the public about the importance of implementing good PHBS practices through counseling by way of explanations through posters, as well as screenings of films containing PHBS messages, so that it is hoped that it can improve people’s behavior in implementing health protocols during the adaptation period of new habits in the midst of the covid-19 pandemic.